Bildung in Crisis: The Hospitality of Negation in Friedrich Schelling's Clara (1810). Issue 3 (4th May 2019) - Gagan, Rebecca
ABSTRACT: This essay proposes that Friedrich Schelling's experimental narrated dialogue, Clara, or, On Nature's Connection to the Spirit World (1810), challenges Enlightenment understandings of Bildung as progressive, linear, and perfected by exploring a model of Bildung as crisis in which development is precarious, contingent, and constantly in revision. Following on the work of educational theorist Deborah Britzman, I read the fragmented structure of Clara and, in particular, the "empty place" in Schelling's manuscript as openings through which to understand Clara 's textual engagement with crisis not as an obstacle that must be overcome, but rather as constitutive of Bildung itself. As a text through which Schelling is thought to have mourned the loss of his wife, Caroline, Clara has mostly been the subject of biographical interpretations and a much wider berth has been given to analyses of the text's central arguments about the obscurity of the categories of life and death, the here and the hereafter, and the sensible and the insensible. By engaging Clara as a text that exceeds its biographical interest and in which Schelling urges hospitality towards negation, we realize the text as an important work not only in Schelling's own oeuvre, but also in our own negotiations with Bildung .